The Effect of Gender and Culture on Loneliness: A Mini Review - Ami Rokach (Ital Publication, 2018)
Loneliness is an experience determined by a person’s characteristics, her situational variables, gender, and background. This review article describes the myriad of studies, with sometimes contradictory results about the relation of loneliness to gender [with women commonly expressing, though not necessarily experiencing, greater loneliness], and the relation between loneliness and collectivistic and individualistic culture.